National Technology Initiative and modern economic shocks - V. V. Medvedev; A. V. Ragutkin; Yu. A. Fedchenkova (Вестник университета)
One of the important macro programs for the development of modern Russia is the National Technology Initiative. It brings together many different projects aimed at accelerating innovative development, building the potential of Russia’s technological leadership in the context of the fourth industrial revolution. Changes in the macroeconomic situation due to anti-Russian sanctions require clarification of the mechanisms for implementing the National Technology Initiative. This determines the relevance of the article.   The purpose of the study is to consider the essence and direction of these changes.   It is shown that in the current economic and political situation, the most promising are projects aimed at forming an independent technological basis for Russia’s development, ensuring the country’s technological sovereignty. This requires a revision of the previously established limits for budget financing of projects of the National Technology Initiative, both in terms of volume and timing of its allocation. There is also a need for the next round of prioritization, which will make the forecast and planned characteristics of the National Technology Initiative more appropriate to the current situation.